New concepts in blood pressure variability - V. M Gorbunov; I. N Posokhov (Российский кардиологический журнал)
A review of the recent literature examines novel concepts in blood pressure variability (BPV) and their possible clinical significance. In our opinion, two approaches are promising, in which the underlying pathophysiological processes are considered in the form of a simple linear and more complex nonlinear model. Moreover, both approaches have a specific practical implementation as follows: the first — in the form of a scale, the second — in the form of new BPV parameters. The scale is intended to assess the severity of systemic hemodynamic atherothrombotic syndrome, which is the result of the synergistic interaction of vascular damage and hemodynamic stress accumulating over a long time. Novel indicators describe the beat-to-beat BPV, reflecting the preservation of regulatory mechanisms. The literature analysis also allowed us to suggest possible ways to improve these concepts.